PASSENGERS SERVICE QUALITY BY AIRLINES IN AIRPORT COMPLEXES - Semchenko, N. O.; Ukrainskyi, Ye. O. (Systems and Technologies, 2023)
In order to increase the competitiveness of airport complexes on the world market of air transport services, enterprises have to pay special attention to quality issues. The primary indicators of the quality of services in aviation are aviation safety, regularity of flights and service. But the range of needs of aviation service users is constantly expanding and the requirements for ensuring their quality are growing. When evaluating the level of aviation service, the passenger perceives the service as a whole. For him, it is not important who provides these services – the airline or the airport. The passenger equates the provision of services exclusively with the results of the airline’s activities. Therefore, airlines are engaged in improving the service, both on the ground and during the flight. The article is devoted to the determination of factors affecting the quality of passenger service in airport complexes. The quality of services is a component of ensuring the competitiveness of airlines. The article presents criteria for evaluating the quality of passenger service in airport complexes, including services on board the plane. A methodology for assessing the quality of airport complex services has been developed. The methodology involves surveying passengers with the aim of obtaining personal and general information about the quality of services provided, identifying shortcomings in passenger service in airport complexes and further improving the quality of their work. Also, the survey will allow to determine the main directions of the management’s work to improve the quality of the airport complex. This, in turn, will lead to an increase in the economic performance of the airport complex. The practical significance of the research results lies in the possibility of using them as a management technique for the service quality system of the airport complex. Separate provisions can be used by airlines for the comprehensive development of the existing competitive potential and the achievement of their successful functioning on the market.